The Relationship Between Cybercrime and the Nigerian Economy: Causes, Implications and the Path Forward - Udoinyang, Nathan; Daniel, Reuben; David, Abroad E (International Journal of Economic, Finance and Business Statistics, 2024)
This research examined the relationship between cybercrime and the Nigerian economy: Causes, implications and path forward. Data from banks and her clients was gathered for this research using a survey approach. Access Bank, First Bank, GT Bank, UBA, and Zenith Bank are some of these banks. In order to get the effects from experts, the University of Port Harcourt's Bursary Department, Ignatius Ajuru University of Education's Computer Science Department, and others were selected. The random sampling approach was used in order to get a sample size of 300 from the intended population. To collect the required data, a self-structured questionnaire titled Cybercrime and the Nigeria Economy: Causes, Implications, and Path forward (C.N.E.C.I.P.F.) was filled out. A total of 300 questionnaires were personally administered to the respondents, 260 copies were retrieved and used for data analysis and interpretations using a simple percentage procedure with aggregate criterion of 50%. Reviewing the causes of cybercrime in Nigeria among others are: Urbanization and civilization; unemployment; poor implementation of cybercrime laws and inadequate equipped law enforcement agency; corruption etc. Our findings also review that the implications of cybercrime on Nigeria’s economy are: disruption of business operation; loss of revenue; monetary losses etc. Although cybercrime cannot be completely eliminated, it may be lessened in intensity, according to the research's findings. The research also made a number of recommendations and concluded that to reduce the extent of cybercrime in Nigeria to a minimum, there is a need for citizens, businesses, and the government to actively collaborate.